Increasing Teacher Creativity Through Strengthening Teamwork, Personality And Work Motivation - Hernaeny, Ul’fah; Notosudjono, Didik; Retnowati, Rita (Kontigensi : Jurnal Ilmiah Manajemen, 2024)
Creativity is a behavior that must be possessed by humans in order to adapt to a rapidly changing environment. The challenges faced in daily life, including at work, make humans creative, both in thinking and in acting. The purpose of this study is to find solutions, namely strategies and ways to improve teacher creativity by examining the influence of other variables on teacher creativity. These variables are teamwork, personality, and work motivation. This study is a non-parametric study because the entire population of 153 private high school teachers in Depok City, West Java, Indonesia, was taken as a sample. Data were collected using questionnaires and analyzed using PLS-SEM (Partial Least Square-Structural Equation Modeling). The results showed that teamwork, personality and work motivation have positive direct and indirect effects on teacher creativity. A discussion of the research findings and their implications as well as suggestions will be discussed further at the end of the article.